Searching for the Missing Link: Trade, Censorship and Human Rights in the Digital Era - GAO, Henry Shuchao (Institutional Knowledge at Singapore Management University, 2010)
For a long time, the relationship between trade law and human rights has been a subject of hot debate between scholars from both trade law and human rights circles. The latest Google episode in China provided yet another chance to revisit the debate. Compared to previous cases, this case is even more intriguing for the following reasons: First, unlike previous cases, which are mostly about the WTO-consistency of trade sanctions adopted in response to alleged human rights violations, the current one is a rare case in which the possibility of using trade law directly to challenge the legality of national measures which are regarded as much as a trade law issue as a human rights issue. Second, and this point apparently relates to the first point, in most of the previous cases the alleged human rights violations affect almost exclusively only domestic individuals or firms, but in the current case the foreign firms are affected as much as, if not more than, the domestic firms. Third, the previous cases are mostly concerned with rules governing trade in goods, while most of the potential legal claims in the current case arise under the GATS, an agreement people are much less familiar with. Fourth, to make the current case even more complicated, the main services at issue are those that only emerged since the dawn of the digital age, and it is highly unlikely that these services were even contemplated when the GATS rules were negotiated. All in all, these unique features make this case an interesting and challenging case study on the relationship between trade and human rights in the digital era.In this article, the author will review the many issues – both theoretical and practical – that this case might raise for the WTO system. Starting with a detailed explanation of the tools of internet control that the Chinese government employs against both domestic and foreign internet service providers, the article will assess the legal merits of a WTO challenge in this case. First, we will try to ascertain the service sector or subsectors that might be at issue. Second, the article will discuss to what extent China has made commitments in each of the identified sector, as well as any limitation or restrictions that has been inscribed for such commitments. Next, we will discuss whether the Chinese internet filtering regime is in violation of these commitments and other relevant GATS obligations. In the fourth part, the article will discuss any exceptions that China might be able to invoke in the case of a breach. The article will conclude the discussion with suggestions on the practical course of action that might be taken in the current case and similar cases in the future, as well as thoughts on how useful the WTO rules may be as a weapon for protecting human rights.